Improving Batik Making Skills Through the Use of Simple Stamp Media in Junior High Schools - Ahyan Giri Pangestu; Tantra Sakre (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to improve the stamping ability of class VIII E students of SMP Negeri 1 Wonosalam through the use of simple stamping media. The method used is Classroom Action Research (CAR) model John Elliot which is implemented in three cycles, including the initial stamping stage, improving stamping techniques, and coloring and rolling. Learning media is developed from simple materials that are easily obtained in the surrounding environment. The results of the study showed a significant increase in students' batik skills, with an average score increasing from 74.2 in cycle I to 77.6 in cycle II, and reaching 85 in cycle III. The application of simple stamping media has proven effective in increasing motivation, active involvement, and student learning outcomes in fine arts learning. This study recommends that fine arts teachers develop contextual learning media based on the environment in order to create a creative, innovative, and enjoyable learning process.